Filtration behaviors in constant rate microfiltration with cyclic backwashing of coagulated sewage secondary effluent - Ohn, Than; Jami, Mohammed Saedi; Iritani, Eiji; Mukai, Yasuhito; Katagiri, Nobuyuki (Taylor & Francis Group, LLC, 2003)
The constant rate microfiltration characteristics of sewage secondary effluent pretreated with polyaluminum chloride (PACl) have been investigated. In order to reduce membrane fouling, the periodic operation of constant rate microfiltration and backwashing cycles was conducted using the fully automated experimental apparatus with the monolithic ceramic membrane module. As filtration proceeded, cake formation occurred on the membrane surface causing an increase in pressure drop. Backwashing could reduce the flow resistance resulted from the formation of the filter cake. However, the initial pressure drop seemed to increase after each backwashing due to the irreversible pore blocking of the membrane. Based on the intermediate blocking law, a mathematical model has been developed to describe the pore blocking behavior. Using the model in combination with the filtration rate equation for the compressible cake the energy consumption has been evaluated for the whole process. The experimental results were in good agreement with those calculated from the theoretical model. Optimum operational conditions for an energy efficient process were suggested based on analytical results. The reclaimed water is found to be free from microorganisms and can be reused in applications such as toilet flushing, car washing.